Mapping Waqf Research: Bibliometric Analysis (UIN Sunan Kudus, 2022)
The purpose of this study is to examine Indonesia's waqf development pattern. Waqf-related research includes, among other things, the study of waqf law, productive waqf schemes, empowering waqf for poverty, stock waqf, and waqf connected to sukuk. The most popular articles are frequently those that discuss how waqf can reduce poverty and promote economic empowerment. Studies on the professionalism of waqf institutions in Indonesia are relatively few. A review of the literature on the management of waqf institutions in favor of professionalism was done by the researchers in light of this. This study is a quantitative investigation that makes use of bibliometric analysis. A quantitative strategy for examining bibliographic information in papers and journals is called bibliometrics. In this study, a waqf journal that Google Scholar has indexed served as the population. Publish or Perish 8 was used to select the samples for this study, which were publications with the keywords